Healing effect of phenytoin on excisional wound in experimental albino rats - Mohua Sengupta; Prithwijit Banerjee; Suhrita Paul; Janmejoy Sengupta; Mainak Ghosh (Wolters Kluwer Medknow Publications, 2015)
Background and Objective: A common side effect with phenytoin is gingival hyperplasia. This apparent stimulatory effect of phenytoin on connective tissue suggested the possibility for its use in wound healing. This study aims to evaluate the effect of 1% and 2% phenytoin ointment on the excisional wound healing process in experimental albino rats, in comparison to 5% betadine ointment. Materials and Methods: Albino rats of Wistar strain (150200 g) were divided randomly into four groups (n = 6). The animals were anesthetized with ether, shaved on the back, and the skin was disinfected using cotton and alcohol wipes. Excisional round, full-thickness skin wounds of diameter 15 mm were created in the paravertebral area, at 5 mm from the midline on the back of all the animals, using sterile disposable acuderm biopsy needle. The following medications were applied topically to the wound twice daily for a maximum of 20 days. Group A rats served as negative control (untreated). Group B rats were applied 5% betadine ointment (positive control). Group C and group D rats had 1% and 2% phenytoin powder applied on them, respectively. Wound healing was measured on days 0, 4, 8, 12, 16, and 20 of the experiment. Number of days taken for complete epithelization of wound was also noted. Statistical analysis was done using analysis of variance (ANOVA) followed by TukeyKramer test and P < 0.05 was considered significant. Results: Both 1% and 2% phenytoin powder hastened healing and reduced the time taken for complete epithelization of excisional wound in albino rats, when compared to negative control (P < 0.05). While 2% phenytoin powder was superior (P < 0.05) to both 1% phenytoin powder and 5% betadine, the latter two were comparable (P > 0.05). Conclusion: 2% phenytoin may be considered as an important agent for wound healing, but its role in the healing of infected wound needs to be explored further.